ANALISIS PENGAARUH KUALITAS LAYANAN DAN STORE ATMOSPHERE TERHADAP KEPUASAN PELANGGAN UNTUK MENCIPTAKAN MINAT MEREFERENSIKAN (Studi Kasus pada Pelanggan Stove Syndicate Coffe & Waffle di Semarang) - Rafsanjani, Ardhy; Sutopo, Sutopo (Diponegoro Journal of Management, 2017)
This study examines the effect of Service Quality and Store Atmosphere on customer Interest in Referencing, with customer Satisfaction as an intervening variable. Respondents are 120 customers who had visited and purchased products at Syndicate Stove Coffe & Waffle Semarang, at least three times. This study develops a theoretical model by proposing five hypotheses to be tested using a multiple regression analysis technique.The result shows that both of independent variables, Service Quality and Store Atmosphere, have a direct effect on customer Interest in Referencing as dependent variable. Service Quality and Store Atmosphere also have a significant positive effect on customer Satisfaction. Therefore, it can be suggested for Syndicate Stove Coffe and Waffle Semarang management to improve their service quality and store atmosphere that influence their customers’ satisfaction in order to create the interest in referencing.